The democratic” selection of leaders in Brazilian Federal Universities: Appointments in the Bolsonaro Government - Honorato, Daniely; Souza, Kellcia Rezende (Revista Hipótese, 2023)
In Brazil, since the administration of Michel Temer (2016-2018), the management of Federal Universities has been subjected to a weakening of financial, administrative, and political autonomy. During Jair Messias Bolsonaro's presidency (2019-2022), this situation intensified and significantly eroded constitutional principles in education, including democratic governance. In this context, this research aimed to analyze Brazilian legislation concerning the democratic management of Federal Universities and its implications during the Bolsonaro administration (2019-2022). Through a qualitative approach, bibliographic research, and document analysis, it was observed that over 25 Federal Universities experienced direct intervention through the appointment of their leaders by the then-President, disregarding the choices made by their respective academic communities. This outcome indicated that, in addition to an authoritarian profile of the government in question, it also benefited from the historical weakness of legislation related to this issue, which does not ensure the full guarantee of the election of leaders by the university community.
Keywords: Democratic management; Federal Universities; University education; Educational politics; Bolsonaro Government